Pengelolaan Transaksi Jual Beli Kayu Pohon Berbasis Prinsip Syariah dan Implikasinya terhadap Kesejahteraan Masyarakat - Fauziah; Aziman, Fauzan; Jumanah; Muhammad Maghfur, Agung (Al-Ijtima`i: International Journal of Government and Social Science, 2026)
This study examines the practice of standing timber transactions in Bingin Teluk Village, Rawas Ilir District, North Musi Rawas Regency, South Sumatra Province, from the perspective of Islamic Economic Law. Although similar transactions are widely practiced in various regions of Indonesia, previous studies have primarily focused on the general concept of gharar without explicitly identifying the applicable contract (akad) or systematically examining the clarity of the transaction object, the suitability of the salam contract, and the implications of uncertainty for contractual validity. This study addresses this research gap by applying three analytical indicators: (1) the fulfillment of the essential elements (rukun) of sale and purchase, (2) compliance with the legal requirements of a salam contract concerning the specification of the transaction object, and (3) the degree and characteristics of gharar embedded in the transaction. The research employed an empirical juridical (socio-legal) approach with a qualitative descriptive design, examining law as both a normative framework and a social practice (living law). Data were collected through structured interviews with ten purposively selected respondents, comprising three timber buyers and seven timber sellers, complemented by documentary analysis of the Qur'an, Hadith, the Compilation of Islamic Economic Law (KHES), and relevant literature on fiqh muamalah. Data were analyzed through data reduction, descriptive-analytical presentation, and conclusion drawing based on triangulation between empirical findings and Islamic legal norms. The credibility of the findings was strengthened through member checking and peer debriefing. The results indicate that the transactions fulfill the essential elements of a valid sale and purchase; however, they fail to satisfy the legal requirements of a salam contract due to the lack of certainty regarding the quantity, species, and condition of the standing trees, thereby constituting gharar, which is prohibited under Islamic law. Beyond the legal dimension, the findings also reveal weaknesses in the governance of community-based timber transactions, reflected in the absence of standardized transaction procedures, object verification, and institutional oversight. The novelty of this study lies in the development of a systematic indicator-based legal analytical framework for assessing the validity of standing timber transactions under Islamic Economic Law, while also proposing collaborative governance involving village authorities, forestry extension officers, religious counselors, and community leaders to strengthen legal certainty, transparency, and compliance with Sharia principles.